PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KINERJA PETUGAS LEMBAGA PEMASYARAKATAN - Abiyyu Gufran; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The term performance comes from the word job performance or actual performance (work performance or actual achievement achieved by an employee in carrying out his duties in accordance with the responsibilities given to him). One of the most important things in an organization to achieve goals is employee performance. The purpose of this study was to determine the extent of the influence of leadership on employee performance. The data and sources used are the results of previous research. Furthermore, the data that has been collected was analyzed using descriptive methods. The results of this study conclude that leadership has a significant effect on work motivation.